The progress of PET/MRI in clinical management of patients with pancreatic malignant lesions - Li, Jindan; Fu, Chaojiang; Zhao, Sheng; Pu, Yongzhu; Yang, Fake; Zeng, Shuguang; Yang, Conghui; Gao, Hongqiang; Chen, Long (Frontiers in Oncology, 2023)
Recently, the morbidity and mortality of pancreatic cancer have been increasing year by year. Because of its deep anatomical location and because most presented patients often suffer from abdominal pain or jaundice, it is difficult to diagnose pancreatic cancer at an early stage, leading to late clinical stage and poor prognosis. integrated positron emission tomography/magnetic resonance imaging (PET/MRI) fusion imaging not only has the characteristics of high resolution and multi-parameter imaging of MRI, but also combines the high sensitivity and the semi-quantitative characteristics of PET. In addition, the continuous development of novel MRI imaging and PET imaging biomarkers provide a unique and precise research direction for future pancreatic cancer research. This review summarizes the value of PET/MRI in the diagnosis, staging, efficacy monitoring, and prognosis evaluation of pancreatic cancer, and prognosis for developing emerging imaging agents and artificial intelligence radiomics in pancreatic cancer.